PENGARSIPAN BUDAYA KOTAGEDE DAN FACEBOOK SEBAGAI REPOSITORI: Array - Wakhid Nur Effendi (Jurnal Kearsipan, 2019)
Efficiency and storage capacity are the main reasons for the social media users to use Facebook as their third party archival repository dan access provider towards their community archives. Two Kotagede cultural practicioners, Erwito Wibowo and Natsir Dabey, are aware for that potential. This article describes how cultural archiving at Kotagede Yogyakarta by preserving and providing access towardss their cultural activities at Facebook repository.